Deep venous thrombosis in a patient undergoing In-vitrofertilization with oocyte donation - Nalini Mahajan; Padmaja Naidu; Shalu Gupta; Kumkum Rani (Wolters Kluwer Medknow Publications, 2015)
Deep venous thrombosis (DVT) has been reported extensively following ovarian hyperstimulation syndrome during in-vitrofertilization (IVF). Pregnancy per seincreases the risk of DVT due to a hypercoagulable state. The long-term use of hormone replacement therapy (HRT) is another critical factor associated with DVT in women. However, an association between the short-term use of HRT in oocyte donation (OD) cycles and DVT has not yet been reported. We present a case of 43-year-old woman who developed DVT after IVF-OD. DVT was diagnosed at 7 weeks of pregnancy and was managed with low-molecular-weight heparin. We suggest that even a short-term use of HRT should be considered a risk factor for DVT especially in the presence of additional risk factors such as obesity. The patient had an uneventful recovery and delivered three healthy though preterm babies.